O Boletim de Ocorrência sob o aspecto da dêixis de base espacial como processo de instauração e manutenção de referência - Roberto Mauro de Souza Tristao (2007)
The research developed in this masters thesis is based on the theory of enunciation, more specifically speaking, on the semantics of enunciation, according to which the natural configuration of language acquires a certain distinctness when associated with an enunciative context, that is, when it is associated with the disposition of the syntactic slots. Moreover, this thesis considers that the relation between language and that which is external to it relies on the sustainability and pertinence of the utterance to specific references, deixis being one of them. This thesis proposes a series of studies related to spatial deixis, based on a corpus of 20 (twenty) police reports by the Military Police of the State of Minas Gerais. These reports were divided into 3 (three) groups: crimes and violations; traffic; and environmental crimes. The research on this particular genre specifically points to the spatial perspectives of both the speaker/military policeman and the speakers/declarants, all involved in the event of report. Besides that, one can notice the use of different strategies of production to ensure that spatial reference is established and maintained: different uses (naming, parameters, and endophoric markers) of the semantic bases of the spatial aspect; grounding by means of spatial references (demonstrative pronouns, adverbs, adjectives, and nouns), a process that enables narrated events to followa sequence in the registers; and encapsulation, which is responsible for the construction of space in the realm of textuality, by means of descriptive data and qualifiers. The studies are based on spatial perspectives associated with different levels of constituted historicity, upto the level of space that has not been historically constituted, besides considering also as space: genre, text and other aspects indicated by means of references that may be recovered by the reader of the reports and that serve as mediators between the space of the text and the space of the world.